1980
DOI: 10.1128/jvi.35.2.340-348.1980
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of secondary modifications of mouse mammary tumor virus proteins by two-dimensional gel electrophoresis

Abstract: The structural proteins of mouse mammary tumor virus (MMTV) were analyzed by two-dimensional electrophoresis on isoelectric focusing and sodium dodecyl sulfate gels. Many of the viral proteins displayed heterogeneity in charge due to variable contents of carbohydrates (in particular, sialic acid) and phosphate residues. Neuraminidase treatment ofthe virions influenced the isoelectric pattern of the envelope glycoproteins. The glycoproteins of an MMTV variant which was attenuated by replication in feline kidney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…2, lane 3). Subsequent analysis (see below) showed that peak a contained a gag protein that was probably the viral gag phosphoprotein previously referred to as pp2l (4,26,27,33). Protein eluting in peak b (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…2, lane 3). Subsequent analysis (see below) showed that peak a contained a gag protein that was probably the viral gag phosphoprotein previously referred to as pp2l (4,26,27,33). Protein eluting in peak b (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…CrFK feline kidney cells have been used extensively both to propagate and to investigate the biology of a number of enveloped viruses, including retroviruses such as feline immunodeficiency virus (FIV) (1,2,6,19,21,27,32), feline leukemia virus (FeLV) (23), mouse mammary tumor virus (MMTV) (13,20,24), herpesviruses (7,35), coronaviruses (3,12), and feline syncytial virus (18). Further, retrovirus vectors based on MMTV (4,25) and FIV (22) have been constructed with CrFK cells.…”
mentioning
confidence: 99%
“…Also, much of the biology of FIV, and to some extent MMTV, has been elucidated with CrFK cells. Indeed, CrFK is one of the few cell lines known to be permissive for production of MMTV (13,20,24). Although it is not clear whether the CrLE virus can act as a helper for FIV or type B viruses, the formation of pseudotypes may also contribute to infection (33).…”
mentioning
confidence: 99%
“…The endoplasmic reticulum seems to play an important role in the synthesis and transport of the MTV envelope antigen. The cell fractionation studies (4,11) indicated that this protein migrated from membrane-bound ribosomes to the plasma membrane via the smooth endoplasmic reticulum and the Golgi apparatus. The staining of these cytoplasmic vesicular structures was not homogeneous in individual cells.…”
Section: Discussionmentioning
confidence: 99%
“…The major envelope protein, gp52, is glycosylated. Glycosylation of the precursor protein of gp52 occurs on membrane-bound ribosomes during its transport through the endoplasmic reticulum to the plasma membrane (4,11). Intracytoplasmic…”
mentioning
confidence: 99%